2014
DOI: 10.1016/j.schres.2013.11.041
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the safety and efficacy of cariprazine in patients with acute exacerbation of schizophrenia: A phase II, randomized clinical trial

Abstract: The results of this study support the efficacy and safety of cariprazine in patients with acute exacerbation of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
180
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(192 citation statements)
references
References 25 publications
9
180
0
3
Order By: Relevance
“…The efficacy and safety of cariprazine in the treatment of patients with schizophrenia have been evaluated in 3 positive randomized, placebo-controlled, phase 2/3 clinical studies. [13][14][15] Post hoc analyses of pooled data from these studies were conducted to investigate the effect of cariprazine on hostility in patients with acute exacerbation of schizophrenia.…”
mentioning
confidence: 99%
“…The efficacy and safety of cariprazine in the treatment of patients with schizophrenia have been evaluated in 3 positive randomized, placebo-controlled, phase 2/3 clinical studies. [13][14][15] Post hoc analyses of pooled data from these studies were conducted to investigate the effect of cariprazine on hostility in patients with acute exacerbation of schizophrenia.…”
mentioning
confidence: 99%
“…Across each cariprazine dose that was evaluated, mean CGI‐I scores at end‐point were between much improved (CGI‐I = 2) and minimally improved (CGI‐I = 3) and significantly different than placebo in the bipolar disorder studies at week 3 ( P  < .001 each)6, 7, 8 and in the schizophrenia studies at week 6 ( P  < .01 each) 9, 10, 11. Additionally, in a previous post hoc pooled analysis of data from the constituent bipolar disorder studies, the rate of CGI‐I response (score ≤ 2, much/very much improved) was significantly greater for cariprazine‐ (64%) vs placebo‐treated (42%) patients ( P  < .0001),19 providing further support for our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…RGH‐MD‐05 (NCT01104779)11 was a fixed/flexible‐dose study with 2 cariprazine treatment arms (3‐6 mg/d or 6‐9 mg/d). RGH‐MD‐16 (NCT00694707)10 was a fixed‐dose study (cariprazine 1.5 mg/d, 3 mg/d or 4.5 mg/d); risperidone was included as an active control. Cariprazine doses were pooled for post hoc analyses in each disease state (schizophrenia, 1.5‐9 mg/d; bipolar mania, 3‐12 mg/d).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In phase II (cariprazine 1.5, 3.0, or 4.5 mg/day) [32] and two phase III (cariprazine 3 to 6 or 6 to 9 mg/day [33]; cariprazine 3 or 6 mg/day [34]) RCTs in patients with acute exacerbation of schizophrenia, cariprazine was effective and generally well tolerated at all doses tested (1.5-9 mg/day). A 26-week phase IIIb RCT of 461 patients with schizophrenia with persistent and predominant negative symptoms showed that cariprazine (target dose 4.5 mg/day) was more effective for negative symptoms compared to risperidone (target dose 4.0 mg/day) [35].…”
Section: New Drugs With Familiar Mechanismsmentioning
confidence: 99%